2021
DOI: 10.1002/1878-0261.12996
|View full text |Cite
|
Sign up to set email alerts
|

A DNA damage repair gene‐associated signature predicts responses of patients with advanced soft‐tissue sarcoma to treatment with trabectedin

Abstract: Predictive biomarkers of trabectedin represents an unmet need in advanced soft-tissue sarcomas (STS). DNA damage repair (DDR) genes, involved in homologous recombination or nucleotide excision repair, had been previously described as biomarkers of trabectedin resistance or sensitivity, respectively. The majority of these studies only focused on specific factors (ERCC1, ERCC5 and BRCA1) and did not evaluate several other DDR-related genes that could have a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The analysis of data in the literature and the importance of DNA repair mechanisms in tumor progression led us to the characterization of the NER pathway, the DNA repair pathway often implicated in chemoresistance processes [ 35 , 36 , 37 ], in a cohort of STS patients enrolled at the Orthopaedic Oncology Unit of Careggi University Hospital. It has been demonstrated that efficiency changes of DNA repair capacity of NER genes can be related to the presence of single nucleotide polymorphisms (SNPs) that result in altered mRNA expression or protein activity [ 14 ]. A deficiency in the ability to repair DNA damages could therefore alter the response to treatment with a significant positive association between the polymorphism ERCC2 gene, Lys751Gln, but also ERCC1 , Asn118Asn with the improved cisplatin response in osteosarcoma [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of data in the literature and the importance of DNA repair mechanisms in tumor progression led us to the characterization of the NER pathway, the DNA repair pathway often implicated in chemoresistance processes [ 35 , 36 , 37 ], in a cohort of STS patients enrolled at the Orthopaedic Oncology Unit of Careggi University Hospital. It has been demonstrated that efficiency changes of DNA repair capacity of NER genes can be related to the presence of single nucleotide polymorphisms (SNPs) that result in altered mRNA expression or protein activity [ 14 ]. A deficiency in the ability to repair DNA damages could therefore alter the response to treatment with a significant positive association between the polymorphism ERCC2 gene, Lys751Gln, but also ERCC1 , Asn118Asn with the improved cisplatin response in osteosarcoma [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that deficiencies in DNA repair capacity could have a role in affecting the response to DNA damaging agents [ 11 , 12 , 13 ]. At least six major DNA repair pathways, as well as numerous sub-pathways, are involved in the repair of damage [ 11 , 14 ]. In particular, the nucleotide excision repair (NER) pathway ( Figure 1 ) repairs bulky lesions and has been associated with tumor progression and response to chemotherapy [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical and clinical data confirmed feasibility and suggested hints of activity in a fraction of the enrolled patients, emphasizing the need to improve patient selection through the identification of specific predictive factors ( 12 , 13 ). Both drugs under study – trabectedin and olaparib – had already been studied as single agents, looking for predictive factors among the tightly intertwined mechanisms ruled by DNA Damage Response and Repair (DDRR) genes ( 14 24 ). However, potential predictive factors of combined trabectedin+olaparib treatment response have not been investigated, so far.…”
Section: Introductionmentioning
confidence: 99%
“…Trabectedin creates DNA adducts by interfering with active transcription, wherein its activity is dependent on transcription-coupled nucleotide excision repair (TC-NER) ( 25 27 ). NER defects make tumor cells less sensitive to trabectedin damage and high expression levels of ERCC1 and XPG/ERCC5 (“signs” of a proficient NER machinery) have been described as predictive of better response to trabectedin treatment ( 14 16 , 18 ). Tumor cells bearing homologous repair deficiency (HRD) are more sensitive to trabectedin-induced cell death, as they cannot recruit the proper machinery to repair the double-strand breaks (DSBs) generated upon trabectedin treatment.…”
Section: Introductionmentioning
confidence: 99%